ETHICAL METHODOLOGY IN METZ’S THEORY OF UBUNTU - Futter, Dylan (Phronimon, 2016)
In this article I apply Thaddeus Metzâ€™s ethical methodology to the ancient Greek ideal of ÏƒÏ‰Ï†ÏÎ¿ÏƒÏÎ½Î· in order to show that it generates a distorted account of ubuntu. If ubuntu is a virtue concept, then Metzâ€™s analytical method will not reconstruct it â€” because it fails to determine whether ubuntu refers to one of a plurality of fundamental virtues, the fundamental virtue, or virtue itself.